Effect of hardener on mechanical properties of carbon fibre reinforced phenolic resin composites - Sulaiman, Sarina (Taylor's University, 2008)
In this paper the effect of hardener on mechanical properties of carbon reinforced phenolic resin composites is investigated. Carbon fibre is one of the most useful reinforcement materials in composites, its major use being the manufacture of components in the aerospace, automotive, and leisure industries. In this study, carbon fibres are hot pressed with phenolic resin with various percentages of carbon fibre and hardener contents that range from 5-15%. Composites with 15% hardener content show an increase in flexural strength, tensile strength and hardness. The ultimate tensile strength (UTS), flexural strength and hardness for 15% hardener are 411.9 MPa, 51.7 MPa and 85.4 HRR respectively.